The Role of Mitochondria and Oxidative/Antioxidative Imbalance in Pathobiology of Chronic Obstructive Pulmonary Disease - Białas, Adam Jerzy (Oxid Med Cell Longev, 2016)
Chronic obstructive pulmonary disease (COPD) is a common preventable and treatable disease, characterized by persistent airflow limitation that is usually progressive and associated with an enhanced chronic inflammatory response in the airways and the lung to noxious particles or gases. The major risk factor of COPD, which has been proven in many studies, is the exposure to cigarette smoke. However, it is 15–20% of all smokers who develop COPD. This is why we should recognize the pathobiology of COPD as involving a complex interaction between several factors, including genetic vulnerability. Oxidant-antioxidant imbalance is recognized as one of the significant factors in COPD pathogenesis. Numerous exogenous and endogenous sources of ROS are present in pathobiology of COPD. One of endogenous sources of ROS is mitochondria. Although leakage of electrons from electron transport chain and forming of ROS are the effect of physiological functioning of mitochondria, there are various intra- and extracellular factors which may increase this amount and significantly contribute to oxidative-antioxidative imbalance. With the coexistence with impaired antioxidant defence, all these issues lead to oxidative and carbonyl stress. Both of these states play a significant role in pathobiology of COPD and may account for development of major comorbidities of this disease.